The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/978-3-319-56026-7
|View full text |Cite
|
Sign up to set email alerts
|

Reformation and Development in the Muslim World

Abstract: All Middle Eastern countries, with the exception of Israel and Lebanon, profess Islam as their state religion. Islam, whether simply in words or in fact, is woven into the fabric of these societies, affecting everything from the political system, to the social, financial and economic system. Islam is a rules-based system, with the collection of rules constituting its institutions in the quest to establish societies that are just. Allah Commands mankind to behave in a fair and just manner to protect the rights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In addition, we aimed to give a corresponding Islamic value for each sustainable factor included in this model. To that end, we used the Islamic indices created by Askari and Rahmen [67], updated by Askari and Khan [54,68] and Askari and Mirakhor [69] and…”
Section: Description Of the Ardl Model: Sustainable Development Varia...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we aimed to give a corresponding Islamic value for each sustainable factor included in this model. To that end, we used the Islamic indices created by Askari and Rahmen [67], updated by Askari and Khan [54,68] and Askari and Mirakhor [69] and…”
Section: Description Of the Ardl Model: Sustainable Development Varia...mentioning
confidence: 99%
“…In addition, we aimed to give a corresponding Islamic value for each sustainable factor included in this model. To that end, we used the Islamic indices created by Askari and Rahmen [67], updated by Askari and Khan [54,68] and Askari and Mirakhor [69] and published by the Islamic Foundation. We have found that these indices are a sound judge of economic durability and political and social Islamic life.…”
Section: Description Of the Ardl Model: Sustainable Development Varia...mentioning
confidence: 99%
“…The study recommended a set of reforms for Muslim countries. 30 In addition, Sidek, Said, and Hasan manifested the expansion of Islamic development management covering good governance, sustainable development, the progress of waqf and takaful, the advancement of value-based activities, progress in fiqh and legal framework, and the expansion of Islamic principles in other related areas. 31 Lastly, Askari and Khan designed five Islamicity indices to gauge rule conformity: economic, legal, and governance, human and political rights, international relations, and overall Islamicity.…”
Section: Literature Reviewmentioning
confidence: 99%